Permainan Puzzle Estafet dapat Meningkatkan Motivasi Belajar dan Kemampuan Menyimak pada Anak Usia 5-6 Tahun di TK Ulul Albab Kecamatan Paseh Kabupaten Sumedang - Riska Aprilianti (STAI Terpadu Yogyakarta, 2020)
This research aims to increase learning motivation and scrutinized competent for children 5-6 years old. Method of this research is action research. This resulth are that motivation competent and scrutinized competent for children through puzzle estafet is increasingly. This result be proof with cycle I, cycle II and cycle III showed increase are 85-100 % for every indicator.